Women Entrepreneurs and Social Innovation : The Role of Community-Based Enterprises in Economic Development - Muhammad Ali bin Abu Bakar; Ahmad Kamal bin Hassan; Lim Guan Eng (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Women entrepreneurs play a pivotal role in fostering social innovation through the establishment of community-based enterprises. These enterprises not only address social challenges but also contribute significantly to economic development by creating sustainable solutions and opportunities within their communities. This study explores the intersection of women entrepreneurship, social innovation, and community-based enterprises, emphasizing their potential to drive inclusive economic growth. By leveraging local resources and addressing community-specific needs, women entrepreneurs act as catalysts for change, promoting social equity and economic empowerment. The research highlights key success factors, challenges, and strategies adopted by women-led community-based enterprises to achieve long-term economic and social impact. The findings suggest that supporting women entrepreneurs can amplify their contributions to economic development and societal well-being, particularly in underserved areas.